Construção de circunstâncias. Transformação do bairro dos pobres - Luís André Melo Varela Costa (2017)
This dissertation approaches the complex system of circunstances that surrounded the final proposal for the transformation of the "Bairro dos Pobres". Located in Paranhos parish, in the city of Porto, emerges a social set once more occupied and consequently vivid, that has been degrading and today is a remnant of its experience and social strategy. It holds on a reflexion around its own project process: not exactly of the project as the final product, but as the path that is built in thought through the personal experiences and investigation from where onde learns, collects and synthesizes the materials that translate into study, foundations of the final proposal. It is explored, this way, the construction of circunstances that correspond to situations that involve the thought of the author, that surround him and, because he is the seeder of many of them, to these are added those that result from its own personal experience, which significantly distinghish its creator. Study mechanisms, interrogations, memories, readings, approximations in the form of texts are collected and it ends in a last moment of representations in meticulous drawings. An academic course ends with this dissertation, a last exercise that marks the transition from a study cycle to the professional world of architecture.